2019
DOI: 10.12688/f1000research.16642.2
|View full text |Cite
|
Sign up to set email alerts
|

Adverse reactions of dimethyl sulfoxide in humans: a systematic review

Abstract: Background: Dimethyl sulfoxide (DMSO) has been used for medical treatment and as a pharmacological agent in humans since the 1960s. Today, DMSO is used mostly for cryopreservation of stem cells, treatment of interstitial cystitis, and as a penetrating vehicle for various drugs. Many adverse reactions have been described in relation to the use of DMSO, but to our knowledge, no overview of the existing literature has been made. Our aim was to conduct a systematic review describing the adverse reactions observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(16 citation statements)
references
References 104 publications
(359 reference statements)
0
15
0
1
Order By: Relevance
“…Most of the reports, also describing fatalities after the administration of supplement drips, were anecdotal and based on journal investigations [8,9]. The scientific reports and recommendations mainly concern the potential efficacy of the intervention using certain substances [10,11] or safety of the drips, in general [12]. Recently, we published the results of a cross-sectional survey study on the experience of Polish individuals using parenteral supplementation services [2].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the reports, also describing fatalities after the administration of supplement drips, were anecdotal and based on journal investigations [8,9]. The scientific reports and recommendations mainly concern the potential efficacy of the intervention using certain substances [10,11] or safety of the drips, in general [12]. Recently, we published the results of a cross-sectional survey study on the experience of Polish individuals using parenteral supplementation services [2].…”
Section: Introductionmentioning
confidence: 99%
“…The toxicology of these solvents has been studied extensively, with no particular concerns ( 29 , 30 ). Nonetheless, these solvents may exhibit other effects that can potentially influence the outcome of an assay or a system being tested.…”
Section: Discussionmentioning
confidence: 99%
“…The protective effects of DMSO in reducing DNA damage induction have previously been ascribed to its role as a ROS scavenger [ 55 ]. However, studies also showed its toxicity [ 56 ] and diverse effects on cell differentiation [ 57 ], but mostly were related to the administered doses. The concentrations of DMSO used in the literatures were mostly within 2 M [ 21 , 23 , 53 , 58 , 59 , 60 ] but it was reported to cause gross molecular changes, reduce cell viability and induce cytotoxicity for the concentrations above 1% (0.128 M) [ 57 , 61 ].…”
Section: Discussionmentioning
confidence: 99%